2001
DOI: 10.1063/1.1345516
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the first GaN monolayer on the nitridation damage of molecular beam epitaxy grown GaN on GaAs(001)

Abstract: The initial molecular beam epitaxy growth of GaN on GaAs(001) was studied by real-time monitoring of the (3×3) surface reconstruction and its transition to an unreconstructed (1×1). Various growth conditions were established by variation of the V/III ratio, i.e., the Ga flux. We characterized the effect of the first two strained GaN monolayers: a N-terminated GaN (3×3) monolayer and a second unreconstructed (1×1) monolayer. A series of samples were grown under N-rich, Ga-rich, and near-stoichiometric growth co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…The phase transformation observed at higher temperatures may be due to thermodynamic stabilization. The mechanisms responsible for the formation of the metastable nature of zinc-blende GaN phase at higher temperature is proposed, in which the impact of the ionic chemical reaction species impinging on the surface of growing nanoparticles plays a key role in phase transition the of GaN[11,37].The latice parameters of a =3.18 A o and c = 5.166A° for hexagonal phase are consistent with the standard values. The crystal grain size (D p ) of the GaN nanoparticles was calculated from the XRD peaks using Scherrer's formula (4)[31].…”
supporting
confidence: 76%
See 1 more Smart Citation
“…The phase transformation observed at higher temperatures may be due to thermodynamic stabilization. The mechanisms responsible for the formation of the metastable nature of zinc-blende GaN phase at higher temperature is proposed, in which the impact of the ionic chemical reaction species impinging on the surface of growing nanoparticles plays a key role in phase transition the of GaN[11,37].The latice parameters of a =3.18 A o and c = 5.166A° for hexagonal phase are consistent with the standard values. The crystal grain size (D p ) of the GaN nanoparticles was calculated from the XRD peaks using Scherrer's formula (4)[31].…”
supporting
confidence: 76%
“…On the other hand, low growth temperature led to sufficient accumulation of Ga and atomic stacking faults in the wurtzite which has effect on the surface reconstruction of h-GaN [37,38].…”
Section: Xrd Analysismentioning
confidence: 98%
“…In this last process was found that the content of c-GaN increases, by increasing the growth temperature at 700 • C, with a flux of arsenic at 2.4 × 10 −7 Torr [14]. The analysis by reflection high-energy electron diffraction (RHEED) for this layer showed, an initial (3 × 3) reconstruction during the growth of the first GaN monolayer [15]. However, is of great importance an understanding of the relaxation process of c-GaN during the nucleating layer, due to the impact on the final crystal quality.…”
Section: Introductionmentioning
confidence: 95%
“…1(b)) in MBE. This reconstruction was monitored during GaN growth [12] and nitridation of GaAs [11] by supplying a GaAs ð2 Â 4Þ reconstruction with purified N 2 . Jung et al demonstrated with auger electron spectroscopy (AES) that the Ga/N ratio decreases strongly after tempering the sample.…”
Section: Surfacesmentioning
confidence: 99%